2017
DOI: 10.3390/nu9070730
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Citric Acid-Treated Wheat Germ Extract in Lipopolysaccharide-Stimulated Macrophages

Abstract: Until recently, fermentation was the only processing used to improve the functionality of wheat germ. The release of 2,6-dimethoxy-1,4-benzoquinone (DMBQ) from hydroquinone glycosides during the fermentation process is considered a marker of quality control. Here, we treated wheat germ extract with citric acid (CWG) to release DMBQ and examined the anti-inflammatory activity of this extract using a lipopolysaccharide-activated macrophage model. Treatment of wheat germ with citric acid resulted in detectable re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 35 publications
2
27
0
1
Order By: Relevance
“…NF-κB regulates the activation and differentiation of T cells and inflammasomes ( Chi et al, 2015 ; Gan et al, 2016 ). NF-κB p65 is a pivotal transcription factor of M1 macrophages and induces a great amount of inflammatory genes, including TNF-α, IL-1β, IL-6, IL-10, IL-12 and cyclooxygenase-2 ( Jeoung et al, 2013 ; Jeong et al, 2017 ). Inactivation of the NF-κB, Stat3 is related to the potential pro-apoptotic signaling pathways ( Xiang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB regulates the activation and differentiation of T cells and inflammasomes ( Chi et al, 2015 ; Gan et al, 2016 ). NF-κB p65 is a pivotal transcription factor of M1 macrophages and induces a great amount of inflammatory genes, including TNF-α, IL-1β, IL-6, IL-10, IL-12 and cyclooxygenase-2 ( Jeoung et al, 2013 ; Jeong et al, 2017 ). Inactivation of the NF-κB, Stat3 is related to the potential pro-apoptotic signaling pathways ( Xiang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In LPS-treated mice, increased TNF-α in mice brain tissue and iNOS expression in the cytoplasm of hepatocytes were decreased after treatment of citric acid [34]. In a recent study, wheat germ extract with citric acid was reported to inhibit secretion of the pro-inflammatory cytokines, TNF-α, IL-6, and IL-12 and the synthesis of COX-2, as well as phosphorylation of NF-κB p65 and p38 kinase in LPS-activated macrophages [35]. In addition, calcium citrate showed antioxidant enzyme activities, and inhibited NO production by suppression of the expression of pro-inflammatory mediators (NF-κB, iNOS, and COX-2) and cytokines (TNF-α, IL-1β, and IL-6) in LPS-stimulated RAW 264.7 macrophages [36].…”
Section: Compound 1 Downregulated Il-6 and Tnf-α Production In Lps-stmentioning
confidence: 98%
“…The active compound, 1,5-dimethyl citrate (1), was a simple derivative of citric acid present in many plants and fruits [34][35][36][37]. An anti-inflammatory effect of citric acid derivatives has been reported in previous studies [34][35][36][37]. In LPS-treated mice, increased TNF-α in mice brain tissue and iNOS expression in the cytoplasm of hepatocytes were decreased after treatment of citric acid [34].…”
Section: Compound 1 Downregulated Il-6 and Tnf-α Production In Lps-stmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzoquinones have been reported to play important roles in bioenergetic transport, oxidative phosphorylation, electron transport processes, and the inhibition of adipogenesis [1][2][3][4]. 2,6-Dimethoxy-1,4-benzoquinone (DMBQ) is a natural phytochemical present in fermented wheat germ [5], and has been reported to exhibit various biological properties including anti-inflammatory, antitumor, and antibacterial activities [6][7][8]. Recent research has shown that wheat germ extract elicits anti-adipogenic and antioxidant effects in 3T3-L1 adipocytes [9].…”
Section: Introductionmentioning
confidence: 99%